Vpliv tekaškega treninga na moč trupa pri rekreativnih tekačih - Žargi, Miha (Šport (Ljubljana), 2019)
Running is a very common recreational activity. Many recreational runners are aware that running is a great load for the body, so especially in the winter months, they do strength training. Strength training serves as a preventative of injury and for improving running efficiency. Based on the literature, it is not possible to conclude that after the cycle of strength training, running training is sufficient to maintain the acquired strength. The purpose of the study was to determine whether eight weeks of running training affected the change in muscle strength of the torso. The research involved 10 subjects (age 45 +- 12 years, height 1.72 +- 0.09 m, weight 70.8 +- 12.5 kg). After completing the winter strength training cycle, they performed strength tests, which were repeated after eight weeks of running training. The power tests measured the maximum force of the torso lean left and right, the maximum force of the torso extension and the maximum torque of rotation of the torso left and right. All tests were performed under isometric conditions. The results showed that only the maximum force of the torso lean to the right (z = -2.395, p = 0.017) increased statistically significantly. The results of the torso lean to the left showed a trend of increasing the maximum force, while the extension of the torso showed a trend of decreasing the maximum force. Based on the results, it can be concluded that, in the case of recreational runners, eight weeks of training is sufficient to maintain the torso strength during the same period.
Keywords: adults; odrasli; recreation; rekreacija; running; sport; strength training; šport; tek; trening moči